ผลของสารสกัดพืชสมุนไพรและระยะเวลาการแช่ในสารสกัดพืชสมุนไพรต่อคุณภาพของผลิตภัณฑ์มะละกอแก้วเสริมสารสกัดพืชสมุนไพร - ร้องคำ, หทัยทิพย์; ดาจันทา, เกตุการ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2020)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาผลของสารสกัดพืชสมุนไพร จำนวน 2 ชนิด คือ ดอกอัญชัน (Clitoria ternatea L.) และดอกคำฝอย (Carthamus tinctorius L.) และระยะเวลาในการแช่ชิ้นมะละกอในสารสกัดพืชสมุนไพรต่อสมบัติทางเคมี กายภาพ ปริมาณสารประกอบฟีนอลและฤทธิ์การต้านอนุมูลอิสระของผลิตภัณฑ์มะละกอแก้วเสริมสารสกัดพืชสมุนไพร ผลการศึกษาพบว่าระยะเวลาการแช่ชิ้นมะละกอในสารสกัดพืชสมุนไพรที่เพิ่มขึ้น ส่งผลให้ค่าความสว่าง (L*) ของมะละกอแก้วเสริมสารสกัดดอกอัญชันและดอกคำฝอยมีค่าลดลงแต่ปริมาณของแข็งที่ละลายได้ทั้งหมดมีค่าเพิ่มขึ้น ในขณะที่ระยะเวลาในการแช่ชิ้นมะละกอในสารสกัดพืชสมุนไพรทั้งสองชนิดไม่มีผลต่อค่าความแข็งของชิ้นมะละกอแก้วอย่างมีนัยสำคัญทางสถิติระดับความเชื่อมั่น 95 เปอร์เซ็นต์ (P>0.05) ระยะเวลาการแช่ชิ้นมะละกอในสารสกัดพืชสมุนไพรที่เพิ่มขึ้นส่งผลให้มะละกอแก้วมีปริมาณสารประกอบฟีนอล ฤทธิ์ต้านอนุมูลอิสระ DPPH Radical-Scavenging Activity (DPPH) และ Ferric Reducing Antioxidant Power (FRAP) มีค่าสูงขึ้นอย่างมีนัยสำคัญทางสถิติที่ระดับความเชื่อมั่น 95 เปอร์เซ็นต์ (P≤0.05) โดยระยะเวลาการแช่ที่ 90 นาที มีสมบัติการต้านอนุมูลอิสระสูงที่สุด รองลงมาคือ 60 และ 30 นาที ตามลำดับ และมะละกอแก้วเสริมสารสกัดดอกอัญชันมีปริมาณสารประกอบฟีนอลและฤทธิ์ต้านอนุมูลอิสระ (DPPH และ FRAP) สูงกว่ามะละกอแก้วเสริมสารสกัดจากดอกคำฝอย ดังนั้นผลิตภัณฑ์มะละกอแก้วเสริมสารสกัดดอกอัญชันและดอกคำฝอยจึงเป็นผลิตภัณฑ์อาหารแปรรูปจากมะละกอดิบรูปแบบใหม่ที่มีประโยชน์ต่อสุขภาพ คำสำคัญ: มะละกอ ผลิตภัณฑ์มะละกอแก้ว สารสกัดพืชสมุนไพร ระยะเวลาการแช่ This research was aimed to study the effect of two types of herbal plant extracts, including butterfly pea (Clitoria Ternatea L.) and safflower (Carthamus tinctorius L.), as well as immersion times (30, 60, and 90 min) of green papaya in each plant extracts on the quality of physical, chemical, total phenolic contents and antioxidant capacities of sweet dehydrated green papaya. The research data revealed that, the lightness (L*) value of sweet dehydrated green papaya fortified with butterfly pea and safflower extracts tend to decrease as the immersion time increased. Whereas, the value of total soluble solid were found to increase with immersion time increased. The immersion time did not affect to the hardness value of the sweet dehydrated green papaya fortified with both of herbal plant extracts products (p>0.05). For the antioxidant properties, increasing time of immersed green papaya in the extracts showed significant increasing of total phenolic contents, DPPH radical-scavenging capacities (DPPH) and ferric reducing antioxidant power (FRAP) (P≤0.05). The present study concluded that the highest antioxidant properties were found in the products immersed in the extract for 90 min, followed by the samples treated for 60 and 30 min, respectively. Furthermore, the sweet dehydrated green papaya fortified with butterfly pea extract showed higher content of total phenolic and antioxidant activities (DPPH and FRAP) than that found in the sample fortified with safflower extract. Therefore, sweet dehydrated green papaya fortified with butterfly pea and safflower extract products are a new healthy food product made from green papaya. Keywords: Papaya, Sweet dehydrated green papaya product, Herbal plant extract, Immersion time